Experimental Practices in Interdisciplinary Art : Engaging the Margins - Jackson, Jesse Colin,; LaFarge, Antoinette, (Experimental Practices ;, 2025)
Experimental Practices in Interdisciplinary Art presents the work of contemporary artists who are committed to experimenting in the marginal areas where artmaking, practice-based research, and scholarship intersect. Some work in laboratory settings, some in studios, and some in wild landscapes or abandoned buildings. But all are committed to interrogating the way that art is created and positioned in a culture that continues to marginalize artists working across disciplinary boundaries. Their projects range from inquiries into the way surveillance technologies are used to reinforce power structures to collaboratories that help us to re-envision our relationship with the natural world and with each other. In reflecting on their wide-ranging explorations and unusual methods, these unique artists provide fruitful insights for bringing creativity to bear on issues of public import. See Less